New Evidence of Thermally Constrained Plant Cell Wall Lignification - Crivellaro, Alan; Büntgen, Ulf (Trends in plant science, 2020)
Lignin enhances the mechanical strength of plants and enables their intrinsic water transport. Dendrochronological, wood anatomical, and plant physiological evidence now suggests that the degree of lignin deposition is constrained by low temperature. Placing these findings in an ecological context implies rethinking of the global treeline position.
Keywords: Plants; Wood; buněčná membrána; lignin; growth limit; buněčná stěna; Lignin; life form; Cell Membrane; cold extreme; wood anatomy; Cell Wall; rostliny; dřevo; treeline